2022
DOI: 10.3390/jcm11216260
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Disparities in the Prevalence of Depression among Patients Hospitalized with Type 2 Diabetes Mellitus in Spain, 2011–2020

Abstract: (1) Background: Recent reports suggest a decrease in the prevalence of depression among people with diabetes and important sex-differences in the association between these conditions, however data from Spain is sparse. We aim to assess trends in the prevalence of depression and in-hospital outcomes among patients with type 2 diabetes (T2DM) hospitalized (2011–2020) identifying sex-differences. (2) Methods: Using the Spanish national hospital discharge database we analysed the prevalence of depression globally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A study conducted in Germany showed a higher prevalence of DS in women with diabetes (18.8%) than in men with diabetes (13.6%) 30. Similarly, researchers in Spain reported that the prevalence of depression was 3.32 higher in women with diabetes than in men 13. We extended these observations by analysing the interaction between sex and diabetes on the odds of having DS and showing how the clinical burden of diabetes affected men and women living with diabetes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study conducted in Germany showed a higher prevalence of DS in women with diabetes (18.8%) than in men with diabetes (13.6%) 30. Similarly, researchers in Spain reported that the prevalence of depression was 3.32 higher in women with diabetes than in men 13. We extended these observations by analysing the interaction between sex and diabetes on the odds of having DS and showing how the clinical burden of diabetes affected men and women living with diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…Differences by sex have been reported in the prevalence of DS, usually markedly higher among women compared with men 5 6. This disparity is also found in people with diabetes, where the prevalence of having a diagnosis of depression is higher among women than in their male counterparts 12 13. Although some studies have focused on the comorbidity of diabetes and depression,1 14–17 most have not tested for sex differences,18 and the relationship between diabetes and DS from a sex-informed approach, remains an understudied phenomenon 15…”
Section: Introductionmentioning
confidence: 99%